Impact of general hygiene behaviors on oral hygiene among adolescents of Ghaziabad - A cross-sectional study - Iram Ahsan; Ipseeta Menon; Ritu Gupta; Vikram Arora; Dipshikha Das; Asifa Ashraf (Wolters Kluwer Medknow Publications, 2022)
Background: There is the presence of plenty of evidence supporting the unidimensionality of hygiene behaviors inferring oral hygiene and general hygiene is correlated. More than two-third of India's population still lives in rural areas; therefore, this study is also conducted in the rural areas only. Rural areas generally tend to have poor general hygiene behaviors because of sociodemographic and educational factors and that directly affect the oral hygiene behaviors. Aim: The aim of this study is to assess the impact of general hygiene behaviors on oral hygiene among adolescents of Ghaziabad district of Uttar Pradesh. Materials and Methods: Data were collected from 800 adolescents among 510 households from all the four blocks of Ghaziabad district. A pretested questionnaire was used to assess the demographic variables, oral hygiene, and general hygiene behaviors. Oral hygiene was assessed using oral hygiene simplified index, and general hygiene behaviors were recorded using the four indices related to drinking water index (score 0-3), food index (score 0-3), personal hygiene index (score 0-3), and domestic household hygiene index (score 0-6) and one summary hygiene index (SHI; range 0-15). Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) software version 20.0. Results: More than 50% of the study participants had a low level of general hygiene. A significant association was observed between general hygiene (SHI) and oral hygiene of the individuals. Conclusion: The present study demonstrates significant association between general hygiene and oral hygiene behaviors among adolescents.